Clinical Interventions in Systemic Couple and Family Therapy (European Family Therapy Association Series,, 2018)
This timely update presents modern directions in systemic therapy practice with couples and families, focusing on clinical innovations from Italy, Spain, and Portugal. Top therapists discuss their breakthrough family work in treating familiar pathologies such as depression, borderline personality disorder, infidelity, and addictions, providing first-hand insight into meeting relational dysfunction with creativity and resourcefulness. The book applies novel conceptualizations and fresh techniques to complex situations including multi-problem families, involuntary clients, disability-related issues, anorexia, love and sex in aging, and family grief. From tapping into the strengths of siblingship to harnessing the therapeutic potential of the Internet, the book's cases illustrate the rich variety of opportunities to improve client outcomes through systemic couple and family therapy. This practical guide: Demonstrates strategies for therapists to improve practice Exemplifies methods for reducing the gap between clinical theory and practice Identifies multiple dimensions of systems thinking in case formulation and therapy Offers new insights into treating classic and recent forms of psychopathology Provides a representative picture of couple and family therapy in southern Europe Clinical Interventions in Systemic Family and Couple Therapy is of particular relevance to practitioners and clinicians working within couple and family therapy, and is also of interest to other professionals working in psychotherapy and professional mental health services.